Generation Z's Shift in Interpersonal Communication Towards the Javanese Language System - Bagasti, Anas; Haryanti, Yanti (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
The communication process is the most important part of conversation and building relationships. Communication that takes place between two or more people with direct message effects is the definition of interpersonal communication. Interpersonal communication is something that is important for human life, in the communication process language becomes one of the tools for communication. This research aims to examine whether there is a shift in the use of Javanese among generation Z in everyday life. The research used is a case study that focuses on the shift in Javanese communication among Generation Z teenagers. Primary data collection techniques were taken from short interviews with informants or resource persons from Generation Z teenagers born in 2000 to 2010, as well as secondary data obtained through literature and source studies. related sources. Data analysis techniques are carried out simultaneously with the data collection process and to test the validity of the data, source triangulation is carried out to obtain accurate and accountable data. This research will provide an overview of whether there is a shift in the structure of the Javanese language in the generation Z environment during the communication process.